Distribution Characteristics of Dimethylated Sulfur Compounds and Turnover of Dimethylsulfide in the Northern South China Sea During Summer. Issue 2 (20th February 2020) - Zhai, Xing; Song, Yu‐Chen; Li, Jian‐Long; Yang, Jian; Zhang, Hong‐Hai; Yang, Gui‐Peng
Abstract: Spatial distributions of dimethylsulfide (DMS), dimethylsulfoniopropionate (DMSP), and dimethyl sulfoxide (DMSO) in the northern South China Sea were determined in the summer of 2015. The mean concentrations of DMS, particulate DMSP (DMSPp), dissolved DMSP (DMSPd), dissolved DMSO (DMSOd), and particulate DMSO (DMSOp) in the surface seawater were 2.8 ± 1.0, 6.8 ± 1.5, 14.0 ± 3.1, 12.2 ± 3.2, and 9.2 ± 2.6 nmol L −1, respectively. The contributions of three principal removal pathways of DMS were investigated. The average biological production and consumption rates of DMS in the surface seawater were 6.15 ± 1.12 and 4.63 ± 1.32 nmol L −1 day −1 . Deck incubation experiments showed that the photooxidation rates of DMS for different radiation bands followed the order: K UVB > K UVA > K visible light . The DMS photooxidation rates were higher in the coastal waters than in the open ocean, which might be associated with the higher concentrations of dissolved organic matter of terrigenous input. The sea‐to‐air fluxes of DMS ranged from 1.6 to 50.3 μmol m −2 day −1 with an average value of 15.6 ± 11.6 μmol m −2 day −1 . Based on the respective turnover times of DMS, the contributions of biological consumption, photooxidation, and sea‐to‐air exchange to the sink of DMS were 32.6 ± 11.0%, 23.2 ± 8.9%, and 44.1 ± 19.2%, respectively, suggesting that the three removal pathways were all critical to the migration and transformation of DMS in the surface seawater during summer. Plain Language Summary: Dimethylsulfide (DMS) is an important gas that is mainly produced by phytoplankton in seawater. This compound conveys sulfur from the ocean to the atmosphere, playing a significant role in global sulfur cycling. DMS is also an antigreenhouse gas that influences the Earth's radiative budget and has effects on the global climate (Charlson et al., 1987, https://doi.org/10.1038/326655a0 ; Quinn et al., 2017, https://doi.org/10.1038/ngeo3003 ). DMS emission from the ocean to the atmosphere depends directly on its concentration in the surface seawater. In our study, the distribution of DMS and related sulfur compounds were studied for the first time in the northern South China Sea, the largest marginal sea in the western Pacific. Higher concentrations were observed in coastal areas than in the open ocean due to biological activity. Deck incubation experiments were also carried out to assess the relative contributions of three removal pathways of DMS, including biological consumption, photooxidation, and sea‐to‐air diffusion. All three removal processes of DMS were contributors to the turnover of DMS in this study. Key Points: Distributions of biogenic sulfur compounds were measured in the northern SCS for the first time The contributions of different radiation bands to DMS photooxidation were determined The major DMS turnover rates and turnover times were estimated simultaneously